Threat of fertility loss in cancer patients of reproductive age and the current feasibilities of ovarian tissue cryopreservation - A. A. Parokonnaya; E. G. Tyrsina; A. A. Lushnikova; M. I. Nechushkin; E. B. Kampova-Polevaya; I. Yu. Davydova (Опухоли женской репродуктивной системы)
To solve the problem of preserving reproductive function in cancer patients is very urgent today because antitumor treatment comprising different combinations of radio- and chemotherapy and surgery lead to ovarian reserve depletion and premature menopause in repro- ductive-aged women. The authors propose to consider one of the fertility preservation techniques – ovarian tissue cryopreservation. A procedure for cryopreservation is described in detail; its efficiency is evaluated. In the authors’ opinion, this procedure is one of most promising in preserving the sexual material of cancer patients.